Borderline [videorecording (DVD)] - Warden, Jimmy; Weaving, Samara, 1992-; Nicholson, Ray, 1992-; Dane, Eric, 1972- (Magnolia Home Entertainment, 2025)
A bodyguard protects a pop superstar and her athlete boyfriend from a determined stalker in 1990s Los Angeles.